Trance mediums and new media : spirit possession in the age of technical reproduction - Behrend, Heike; Dreschke, Anja; Zillinger, Martin (Fordham University Press, 2015)
Ongoing debates about the 'return of religion' have paid little attention to the orgiastic and enthusiastic qualities of religiosity, despite a significant increase in the use of techniques of trance and possession around the globe. Likewise, research on religion and media has neglected the fact that historically the rise of mediumship and spirit possession was closely linked to the development of new media of communication. This innovative volume brings together a wide range of ethnographic studies on local spiritual and media practices. Recognizing that processes of globalization are shaped by mass mediation, the volume raises questions such as: How are media like photography, cinema, video, the telephone, or television integrated in seances and healing rituals? How do spirit mediums connect with these media?